Heterogeneous catalytic oxidation of methylene blue by amine-functionalized titanium-terephthalate metal organic framework, NH2-MIL-125 (Ti) - Teo, Szea Err (2017)
Iron oxide sludge formation, high pH dependency, and poor catalyst reusability have always been critical drawbacks of Fenton’s reagent. In this work, titaniumterephthalate metal organic framework, NH2-MIL-125(Ti), was proposed as heterogeneous Fenton-like catalyst for methylene blue degradation. NH2-MIL- 125(Ti) is a metal-organic compound possessing high surface area, photocatalytic properties and unique dual-porosity. MIL-125(Ti) and NH2-MIL-125(Ti) was prepared through reflux method and activated using conventional solvent exchange method. Both samples were confirmed by XRD and FTIR. SEM images showed that NH2-MIL-125(Ti) has spherical morphology with size ranging from 250 to 500 nm which is at least half of the size of MIL-125(Ti). NH2-MIL-125(Ti) is stable under water with superior adsorption and photocatalytic activities upon visible and UV-A irradiation. Furthermore, the results revealed that NH2-MIL-125(Ti) is an effective non-ferrous Fenton-like catalyst. Synergistic effect was observed between NH2-MIL- 125(Ti) and H2O2, with 84 % of removal efficiency in 40 ppm of methylene blue. Results showed that •OH and h+ are the dominant species in Fenton-like oxidation of NH2-MIL-125(Ti)/H2O2 catalytic system. Photoenhancement was proven to be effective where up to 92 % removal was obtained when exposed to UV-A light. NH2-MIL-125(Ti) showed low pH dependency with stable degradation from pH 3 to 9. Negligible amount of titanium leaching was detected which indicates the high stability of heterogeneous NH2-MIL-125(Ti) catalyst with reusability up to three runs. The heterogeneous titanium-terephthalate metal organic framework catalyst can overcome the disadvantages of traditional homogeneous Fenton catalyst. The results indicate that NH2-MIL-125(Ti) can be a new material for Fenton-like oxidation processes.